Handep Hapakat: Solidaritas Sosial pada Tradisi Manugal Orang Bakumpai di Desa Mangkahui Kabupaten Murung Raya - Ruswati, Anis; Budhi, Setia (Huma: Jurnal Sosiologi, 2025)
Manugal is a traditional collective farming practice that persists as a communal activity reflecting the values of social solidarity and cooperation in rice planting among the Bakumpai community in Mangkahui Village. This tradition embodies togetherness, cooperation, and a sense of shared responsibility that form the foundation of local social relations. The study aims to reveal the forms of social solidarity embedded in the practice of handep hapakat. A qualitative method with a case study approach was employed, using data collection techniques such as observation, unstructured interviews, and documentation. The findings show that handep hapakat not only functions as a joint strategy to accelerate the manugal process but also strengthens social solidarity across economic, social, and cultural identity dimensions. Mechanical solidarity is evident in the sense of kinship, trust, and moral obligation to help one another. Academically, this research suggests that future studies develop comparative analyses with similar traditions in other regions, employing multidisciplinary approaches to explore not only the social but also the economic and environmental dimensions, and testing manugal traditions through various social theories such as Durkheim’s solidarity or Dahrendorf’s conflict theory to enrich scholarly perspectives. Practically, the findings can serve as a basis for local governments, customary institutions, and communities to design programs for preserving the manugal tradition through cultural festivals or local education, while also adapting its solidarity values into modern forms of gotong royong that reinforce social cohesion.